Flash cold sintering: Combining water and electricity. Issue 15 (December 2020) - Kermani, Milad; Biesuz, Mattia; Dong, Jian; Deng, Huaijiu; Bortolotti, Mauro; Chiappini, Andrea; Reece, Michael J.; Sglavo, Vincenzo M.; Hu, Chunfeng; Grasso, Salvatore
Abstract: An innovative sintering method that combines Flash (i.e. electricity) and Cold Sintering (i.e. water or other liquid) is presented. The electrolysis of water triggers Flash Cold Sintering (FCS) of ZnO at room temperature without the need for external heating. In the best case, ZnO pellets were sintered up to 96.5 % relative density in less than 60 s by applying 20 V and increasing stepwise the current up to 30 A. The water allows the current to flow across the sample to initiate the flash cold sintering. Interestingly, the photoluminescence properties of flash cold sintered ZnO are rather different to those of conventionally sintered material. This is because flash cold sintering allows the consolidation of ZnO while preserving the defect structure of the starting powder. The use of low voltage and the absence of an external heating make FCS a highly energy saving technique that is potentially suitable to densify other oxides.